Does class matter? Class structure and worsening inequality in India - Vakulabharanam, Vamsi (2010)
Does class structure matter in understanding the increasing inequality in India during the period of economic liberalisation? There is now clear evidence from the National Sample Survey quinquennial household consumer expenditure surveys conducted in 1993-94 and 2004-05 that increased distance between urban elites (owners, managers and professionals), rural rentier classes (such as moneylenders and absentee landlords) that are more stratified at the top, and unskilled urban workers, marginal farmers and agricultural workers, who are increasingly more stratified at the bottom, helps us understand the distributional dynamics of the Indian growth story. This paper analyses the class structures in India and decomposes the overall inequality into inter-class and intra-class terms. it explains these changes by analysing the Indian policies during this period. - Reproduced.
Keywords: Class structure - India; Class structure